2023
DOI: 10.1111/jgh.16304
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of endoscopic ultrasound‐guided tissue sample acquisition for commercially available comprehensive genome profiling

Abstract: Background and AimOptimal tumor samples are crucial for successful analysis using commercially available comprehensive genomic profiling (CACGP). However, samples acquired by endoscopic ultrasound‐guided tissue acquisition (EUS‐TA) are occasionally insufficient, and no consensus on the optimal number of needle passes required for CACGP exists. This study aimed to explore the optimal number of needle passes required for EUS‐TA to procure an ideal sample fulfilling the prerequisite criteria of CACGPs.MethodsPati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…6,49 In addition, using 19G or 22G needles at the first puncture achieves more favorable histological suitability than using a 25G needle. 25 Although several reports have suggested that 1-4 punctures are appropriate for CGP tests, 25,49,50 the present study demonstrated that the sample volume increased with the improvement of the formalin fixation process, regardless of needle type, needle thickness, or the number of punctures. This finding indicates that the oil blotting paper method may increase the available specimen volumes on the glass slide, thus improving the EUS-TA technique.…”
Section: Discussioncontrasting
confidence: 64%
“…6,49 In addition, using 19G or 22G needles at the first puncture achieves more favorable histological suitability than using a 25G needle. 25 Although several reports have suggested that 1-4 punctures are appropriate for CGP tests, 25,49,50 the present study demonstrated that the sample volume increased with the improvement of the formalin fixation process, regardless of needle type, needle thickness, or the number of punctures. This finding indicates that the oil blotting paper method may increase the available specimen volumes on the glass slide, thus improving the EUS-TA technique.…”
Section: Discussioncontrasting
confidence: 64%
“…reported that in a cohort of 98 patients who underwent EUS‐TA (82 pancreas target organ), the adequacy rate for CACGP testing was significantly higher with a 19‐G FNB needle (72.5%), compared with 22‐G FNB (53.5%) and 22‐G FNA (33.3%) needles 6 . The current study adds to the existing literature by further clarifying technical details needed to obtain sufficient tissue sample for improving the success rate of CACGP testing 3 …”
mentioning
confidence: 72%
“…In this issue of Journal of Gastroenterology and Hepatology , Ishikawa et al . examined factors for optimization of EUS‐FNB for CGP using F1CDx 3 . This was a retrospective observational study in which EUS‐FNB had been performed in 393 patients, predominantly PDAC (283 patients, 72%), of which 54 underwent F1CDx analysis.…”
mentioning
confidence: 99%
“…One retrospective study suggested the number of passes was associated with successful CGP tests in 22‐gauge needles, but not in 19‐gauge needles. 37 The appropriate number of passes both for 19‐ and 22‐gauge needles should be further evaluated in the context of CGP tests.…”
Section: Discussionmentioning
confidence: 99%